2001
DOI: 10.1161/hc3601.095932
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutation in the Stalk of Angiotensin-Converting Enzyme Causes a Dramatic Increase in Serum Angiotensin-Converting Enzyme But No Cardiovascular Disease

Abstract: Background-Angiotensin-converting enzyme (ACE) metabolizes many small peptides and plays a key role in blood pressure regulation. Elevated serum ACE is claimed to be associated with an increased risk for cardiovascular disease. Previously, two families with dramatically increased serum ACE were described, but no systematic survey of affected individuals was performed, and the molecular background of this trait is unknown. Methods and Results-Eight families were identified with autosomal dominant inheritance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 38 publications
0
70
0
2
Order By: Relevance
“…Indeed, a variety of animal studies and clinical trials have shown that the inhibition of somatic ACE may prevent the decrease in the bioavailability of nitric oxide associated with "endothelial dysfunction" and/or restore endothelial function (Dzau et al, 2002). The physiological/ pathophysiological relevance of soluble ACE is unclear (Xiao et al, 2004) and although a point mutation in the juxtamembrane stalk of ACE causes a dramatic increase in serum ACE levels but no clinical abnormalities (Kramers et al, 2001), elevated plasma ACE levels have been reported to represent a risk factor for cardiovascular diseases (Cambien et al, 1994;Oosterga et al, 1997).…”
mentioning
confidence: 99%
“…Indeed, a variety of animal studies and clinical trials have shown that the inhibition of somatic ACE may prevent the decrease in the bioavailability of nitric oxide associated with "endothelial dysfunction" and/or restore endothelial function (Dzau et al, 2002). The physiological/ pathophysiological relevance of soluble ACE is unclear (Xiao et al, 2004) and although a point mutation in the juxtamembrane stalk of ACE causes a dramatic increase in serum ACE levels but no clinical abnormalities (Kramers et al, 2001), elevated plasma ACE levels have been reported to represent a risk factor for cardiovascular diseases (Cambien et al, 1994;Oosterga et al, 1997).…”
mentioning
confidence: 99%
“…7 Several DNA-mutations in the ACE gene that cause hyperactivity of ACE have been reported. 8,9,12,13 In the Netherlands, the Pro1199Leu missense mutation seems not uncommon. The prevalence is not known; however, on average we identify one patient with familial ACE hyperactivity per 600 ACE measurements.…”
Section: Discussionmentioning
confidence: 99%
“…ACE enters the circulation by its highly regulated proteolytic cleavage from the cell surface of mainly pulmonary and renal endothelial cells. 8,9 Sarcoid granulomas may produce ACE, which explains the elevated serum ACE activity in about 60-70% of patients with active sarcoidosis. 3 Studies have found that the serum ACE activity level correlates with the granuloma burden.…”
Section: Sarcoidosismentioning
confidence: 99%
See 1 more Smart Citation
“…Greater immune activity at the inflammation sites (i.e., granulomatous lesions) and higher U Ca (as a result of higher cellular immune system activation at the inflammation sites) can be associated with greater antibody titer, as observed in our study. The negative association of ACE level with antibody response could be questioned because serum ACE level is under the influence of several factors 26 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%